Relative Abundance of Floating Plastic Debris and Neuston in the Eastern North Pacific Ocean - Egger, Matthias; Quiros, Lauren; Leone, Giulia; Ferrari, Francesco; Boerger, Christiana M.; Tishler, Michelle (Frontiers in Marine Science, 2021)
Despite an increasing research conducted on ocean plastic pollution over the last decade, there are still large knowledge gaps in our current understanding of how floating plastic debris accumulating in subtropical oceanic gyres may harm the surface-associated pelagic community known as neuston. Removing floating plastic debris from the surface ocean can minimize potentially adverse effects of plastic pollution on the neuston, as well as prevent the formation of large quantities of secondary micro- and nanoplastics. However, due to the scarcity of observational data from remote and difficult to access offshore waters, neuston dynamics in subtropical oceanic gyres and thus the potential impacts of plastic pollution as well as of cleanup activities on the neuston remain uncertain. Here, we provide rare observational data of the relative distribution of floating plastic debris (0.05–5 cm in size) and members of the neuston in the eastern North Pacific Ocean. Our results reveal that the dominant neustonic species co-occurring with high concentrations of floating plastic debris in the North Pacific Garbage Patch (NPGP) such as Porpita porpita, Halobates spp., pteropods, isopods, heteropods, and crabs depict either a low atmospheric drag due to physical attributes or a potential plastic-associated fitness benefit such as increased surface area for oviposition and structure for habitat. We further observe relatively higher plastic to organism ratios inside the NPGP for most target species compared to waters outside the NPGP. The findings presented here provide a first observational baseline to develop ecological models that can help evaluate the long-term risks of plastic pollution and of offshore cleanup activities for neuston in the eastern North Pacific Ocean. We further suggest that offshore mitigation strategies aiming at removing floating plastic debris from the ocean surface need to evaluate both, the direct impact of neuston bycatch during plastic removal on neuston population dynamics, as well as the potential benefits of reducing the negative effects of plastic pollution on the neuston.